Corporate carbon reduction pledges: An effective tool to mitigate climate change? - Stephen Comello; Julia Reichelstein; Stefan Reichelstein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
In the intensifying public debate about limiting the harmful effects of climate change, many global corporations have recently articulated so-called 'net-zero' goals for reducing and ultimately eliminating their own greenhouse gas emissions. We first examine the details ofthe carbon reduction goals articulated by seven large firms in different industries. The individual reduction goals are shown to vary substantially in terms of specificity and scope, largely due to variations in the measurement of carbon footprints. Particular sources of variation arise from how 'gross emissions' are determined and from firms' willingness to recognize carbon credits that offset their own emissions.
Keywords: Q28; Q40; M41; M48; 330; Carbon Emissions; corporate reporting; net-zero goals; carbon offsets